Estimación de parámetros genéticos para la producción de leche en el día del control empleando un modelo de regresión aleatoria para primeras lactancias en búfalos de la costa norte de Colombia - Hurtado-Lugo, N. [UNESP]; Cerón-Muñoz, M.; Tonhati, Humberto [UNESP]; Bignardi, A. [UNESP]; Restrepo, L.; Aspilcuelta, R. [UNESP] (My University, 2009)
A total of 5575 monthly test-day yield records from 796 lactations buffaloes first in the north coast of Colombia. The model included random direct additive genetic and permanent environment effects. As fixed effects were included, contemporary groups, and age of cow at calving as covaraible, linear and quadratic effects. Test-day (PLDC) yield was 3.89 ± 1.14 kg. The PLDC ranged from 2.86 kg to 4.26 kg while the highest values towards the middle of lactation. The heritability estimates obtained for PLDC ranged from 0.23 to 0.47. Genetic correlations between PLDC, declining steadily increased the distance between PLDC. Phenotypic variances were higher in the initial PLDC and decreasing towards the end of lactation. The results found in this study indicate that there is a high genetic variability for the PLDC in the population studied using a random regression model.
Estimates of genetic parameters for test-day using a random regression model for first lactations of buffalo in Colombia north coast
Keywords: Genetic improvement; Legendre's polynomials; Bubalus